The adaptation and norming of selected psychometric tests for 12- to 15- year-old urbanized Western Cape adolescents - Ferrett, Helen Louise (Stellenbosch : Stellenbosch University, 2011)
Thesis (PhD)--Stellenbosch University, 2011.